ҚАРАҚАЛПАҚСТАНДА ШОРАЛАР ҲӘКИМИЯТЫНЫҢ КАДРЛАР СИЯСАТЫ ҒӘРЕЗСИЗЛИК НӘЗЕРИНЕН - Базарбаев, Р.Ж. (SCIENCE and SOCIETY, 2016)
The article deals with the staff policy of Soviet power in Karakilpakstan from the point of view of ideology of national independence. The author also studies the antinational direction of the staff policy of Soviet power in Karakalpakstan.
Keywords: period of Soviet power; dictatorship of proletariat; staff policy; policy of movement